A new approach for concurrently improving performance of South Korean food waste valorization and renewable energy recovery via dry anaerobic digestion under mesophilic and thermophilic conditions - Nguyen, Dinh Duc (Waste management (New York, N.Y.), 2017)
Copyright © 2017 Elsevier Ltd. All rights reserved.